Da psicogênese a sociogênese: por uma interação radical no modelo dialético de Jean Piaget - Arendt, Ronald João Jacques (1988)
The core idea of this thesis 15 that the dialectical interaction between the individual and the environment, which constitutes the basis of the piagetian theoretical model, has to be necessarly a radical interaction. Following an observation of Piaget that, ln the genetic psychology and episthemology the knowlege relation has been studied prioritarly from the subject's and not the object's point of view, this thesis tries to develop the posslbl11ties openned by this exploration, when one considers the expression 'environment' ln its more abrangent conception. Including not only physical but a1so social objects. Dlscussing the sociological critic of the piagetian model, which criticises it for failing to include in it the social dimension, this thesis will / defend the hypothesis that no omission has been made: the social dimension would be inserted in the very interaction concept. With antropological arguments about the space discontinuity, series of generalizations are made which, finally, suggest an enrichment of the piagetian theory understood from the object's point of view. The propositions of this new model give the basis for its application to the solut1on of social and psycholog1cal cognitive problems: a crit1cal discussion is made of the debate between the researchers of the São Paulo University and the Pernambuco Federal University, concerning the intelligence of the brazilian margina child; the analisys of this debate permits to bring the cognitive construction to an antropological and political reference. The thesis ends indicating the correlation of psychogenesis and sociogenesis, compreended from the point of view developed, with the community psychology and the institutional analisys.